Alcohol and substance use diagnoses among HIV-positive patients receiving care in NYC clinic settings. (1st November 2017) - Gurung, Sitaji; Ventuneac, Ana; Cain, Demetria; Mirzayi, Chloe; Ferraris, Christopher; Rendina, H. Jonathon; Sparks, Martha A.; Parsons, Jeffrey T.
Highlights: Immunocompromised patients were found to be lower in the reference group. The reference group was significantly younger than the three comparison groups. Diagnosis of alcohol and drug use was significantly associated. Higher proportion of patients in all three comparison groups had an inpatient stay. HIV treatment providers should routinely screen for alcohol and substances. Abstract: Background: Substance use among HIV-positive persons exacerbates health problems. This study sought to estimate the prevalence of alcohol and drug-use diagnoses and examined hypothesized predictors associated with alcohol and drug-use diagnoses among HIV-positive patients in New York City (NYC). Methods: This cohort study reviewed electronic medical records (EMRs) of 4965 HIV-positive patients based on diagnostic codes. These patients attended a comprehensive care clinic in NYC in 2012. Multinomial logistic regression was used to predict the odds of classification into substance use diagnosis grouping. Results: Of the full sample, only 12.7% of patients had an alcohol use diagnosis documented in their EMR compared with more than one-quarter (26.4%) of patients having a recorded drug use diagnosis ( p < 0.001). Compared with the No Alcohol or Drugs group, the regression model showed that older age and having a recent inpatient hospital stay independently predicted being in the Alcohol Only group; years living with HIV, having an unsuppressed viral load, and having a recent inpatient hospital stay were associated with higher odds of being in the Drugs Only and Alcohol and Drugs groups; and being women and men who have sex with men (MSM) were associated with decreased odds of being in the Drugs Only and Alcohol and Drugs groups. Conclusions: Substance use diagnosis was associated with viremia and low CD4 counts and hospital stays. This implies that providers should screen for substance use in HIV-positive patients with poor health. Further examination of the extent of such comorbidity is instrumental for intervention efforts.